2018
DOI: 10.1007/s10714-018-2484-z
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-local energy from a Minkowski reference

Abstract: The specification of energy for gravitating systems has been an unsettled issue since Einstein proposed his pseudotensor. It is now understood that energy-momentum is quasi-local (associated with a closed 2-surface). Here we consider quasi-local proposals (including pseudotensors) in the Lagrangian-Noether-Hamiltonian formulations. There are two ambiguities: (i) there are many possible expressions, (ii) they depend on some non-dynamical structure, e.g., a reference frame. The Hamiltonian approach gives a handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It was found that for any closed 2-surface there exists a common value for the quasi-local energy for all expressions that agree (to linear order) with the Freud superpotential. In other words, all the quasi-local expressions in a large class yield the same energy-momentum [53,54].…”
Section: Introductionmentioning
confidence: 98%
“…It was found that for any closed 2-surface there exists a common value for the quasi-local energy for all expressions that agree (to linear order) with the Freud superpotential. In other words, all the quasi-local expressions in a large class yield the same energy-momentum [53,54].…”
Section: Introductionmentioning
confidence: 98%
“…The rehabilitation of energy-momentum complexes concerns the searching for a common quasi-local energy value. Recently, an important discovery has been made, namely, by considering pseudotensors and quasi-local approaches in the context of the Hamiltonian formulation and with the choice of a four-dimensional isometric Minkowski reference geometry on the boundary, it is found that for any closed 2-surface there is a common value for the quasi-local energy for all expressions that are in agreement (to linear order) with the Freud superpotential or, put simply, all the quasi-local expressions in a large class yield the same energy-momentum [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for any closed 2‐surface there exists a common value for the quasi‐local energy for all expressions agreeing (to linear order) with the Freud superpotential. Put differently, all quasi‐local expressions in a large class lead to the same energy‐momentum (Chen et al 2018a, 2018b). Furthermore, the localization of energy was studied in the context of teleparallel theory of gravitation whereby many similar results were obtained (Aygün et al 2018; Ganiou et al 2018; Hayashi & Shirafuji 1979; Maluf et al 2007; Møller 1964; Nashed 2010; Nester et al 2008; Sharif & Jawad 2011; Sousa et al 2010).…”
Section: Introductionmentioning
confidence: 99%